2018
DOI: 10.1158/2326-6066.cir-17-0113
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Associated with Human Ovarian Tumors Harbor a Reversible Checkpoint of T-cell Responses

Abstract: Nano-sized membrane-encapsulated extracellular vesicles isolated from the ascites fluids of ovarian cancer patients are identified as exosomes based on their biophysical and compositional characteristics. We report here that T cells pulsed with these tumor-associated exosomes during TCR-dependent activation inhibit various activation endpoints including translocation of NFκB and NFAT into the nucleus, upregulation of CD69 and CD107a, production of cytokines and cell proliferation. Additionally, the activation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 38 publications
(46 reference statements)
3
80
0
Order By: Relevance
“…It has been reported that TEVs reprogram CD8 + T cells to become suppressor cells inhibiting proliferation of other T cells (40). TEVs also inhibit T cell proliferation and cytolytic activity in effector T cells and other effector immune cells such as natural killer cells, and promote regulatory T cell proliferation and formation of myeloid-derived suppressor cells through their immunosuppressive cargo (9,(40)(41)(42). Of note, cytotoxic activity of CD171-specific CAR T cells was independent of NTRK2 expression, which is a marker of aggressive neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TEVs reprogram CD8 + T cells to become suppressor cells inhibiting proliferation of other T cells (40). TEVs also inhibit T cell proliferation and cytolytic activity in effector T cells and other effector immune cells such as natural killer cells, and promote regulatory T cell proliferation and formation of myeloid-derived suppressor cells through their immunosuppressive cargo (9,(40)(41)(42). Of note, cytotoxic activity of CD171-specific CAR T cells was independent of NTRK2 expression, which is a marker of aggressive neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…As the name suggests, internalization is performed by measuring the uptake of a protein/cell or other material into a specific cell. More recently, this feature has been utilized to determine exosome uptake into a cell .…”
Section: Advanced Techniques In and Management Of Flow Cytometrymentioning
confidence: 99%
“…Exosomes are nano-sized (50–100 nm in diameter) membrane-bound vesicles released by a variety of cell types, especially abundantly by tumor cells 19 . Recent evidence has highlighted a role for hypoxic tumor cell-derived exosomes in promoting tumor progression 20 .…”
Section: Introductionmentioning
confidence: 99%